Transitioning in Thailand Online - Enteen, Jillana Beth (AoIR Selected Papers of Internet Research, 2013)
This paper argues, via transnational cyberculture studies and the examination of English language websites generated in Thailand marketing gender-related surgeries, that both sexuality and gender are diffuse sets of social, political, and interpersonal expectations with particular histories and effects. It shows three distinct websites generated in Thailand to attract Western medical tourists by depicting bodies in transition: both from the perspectives of sex/gender surgeries and transnational travel. The shifting strategies and multiple translations deployed by the Thai medical tourism industry via an online presence, which have been compiled in a database that spans three years, are suggested through these three representative websites.